Venezuela-CARICOM. Where are we going in our trade relation? - HERNANDEZ, Oscar (1994)
Points out that the Caribbean Community should view the establishment of closer economic relations between the Caribbean and Latin American states as a must because of proximity, and the need by the Caribbean to diversify external economic relations. On the other hand, the Caribbean countries should be seen by Latin America as a strategic commercial area since it is the only group of developing countries to have preferential access to three major world markets : the US (through the CBI), Canada (through CARIBCAN, and possibly NAFTA), and the EC (through the Lome Convention). Highlights Venezuela's trading performance.